Assessment of Solid Waste Management Practices in Rural Bangladesh: A Case Study of Citizen Participation (Research in Agriculture Livestock and Fisheries, 2024)
Bangladesh's rural solid waste management (SWM) systems are still developing, and effective citizen participation is crucial for SWM success. This study highlights knowledge gaps, as the existing policies focus predominantly on urban areas.In this study, citizen participation, existing practices, and the community engagement of SWM were examined in the rural areas of Bangladesh. Primary data collected from 67 Bangladeshi respondents through questionnaires using a qualitative and quantitative mixed-methods study. The data were analyzed using descriptive statistics. This study found that Bangladeshi rural citizens participate in SWM "personally." Results showed that 41.9% of respondents often dump waste in pits or lowlands near their homes, and a general practice was to discard waste by digging a hole (54.8%) or burying it (41.9%). Household backyards (41.9%) and shallow terrain (48.4%) were used as dumping stations. Different indigenous systems and practices were observed in the rural areas due to the lack of formal SWM. Respondents mentioned that the informal sector recycles plastic, paper, glassware, etc., and a few citizens generate compost from organic waste. Citizens reported that they needed SWM training from rural local governments. Moreover, SWM efforts in rural Bangladesh did not involve citizen groups or associations. In conclusion, local governments can coordinate SWM policy by including citizens for a sustainable environment, and policymakers will have a scope to improve rural SWM in Bangladesh. Furthermore, this paper provides practical implications for researchers and policymakers on SWM in developing countries.Vol. 10, No. 3, December 2023: 301-318